When Concurrency Matters: Behaviour-Oriented Concurrency - Luke Cheeseman; Parkinson, Matthew J.; Clebsch, Sylvan; Kogias, Marios; Drossopoulou, Sophia; Chisnall, David; Wrigstad, Tobias; Liétar, Paul (Proc. ACM Program. Lang., 2023)
Expressing parallelism and coordination is central for modern concurrent programming. Many mechanisms exist for expressing both parallelism and coordination. However, the design decisions for these two mechanisms are tightly intertwined. We believe that the interdependence of these two mechanisms should be recognised and achieved through a single, powerful primitive. We are not the first to realise this: the prime example is actor model programming, where parallelism arises through fine-grained decomposition of a program’s state into actors that are able to execute independently in parallel. However, actor model programming has a serious pain point: updating multiple actors as a single atomic operation is a challenging task. We address this pain point by introducing a new concurrency paradigm: Behaviour-Oriented Concurrency (BoC). In BoC, we are revisiting the fundamental concept of a behaviour to provide a more transactional concurrency model. BoC enables asynchronously creating atomic and ordered units of work with exclusive access to a collection of independent resources. In this paper, we describe BoC informally in terms of examples, which demonstrate the advantages of exclusive access to several independent resources, as well as the need for ordering. We define it through a formal model. We demonstrate its practicality by implementing a C++ runtime. We argue its applicability through the Savina benchmark suite: benchmarks in this suite can be more compactly represented using BoC in place of Actors, and we observe comparable, if not better, performance.